MANAGEMENT INFORMATION SYSTEMS PLAY AN IMPORTANT ROLE IN COMPANIES - Hasanah, Malika Ardhia; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
This research aims to find out that management information systems play an important role in companies that have progressed to become an important part of the company or organization. Apart from that, management systems play an important role in business, in an organization or company it will not run smoothly if there is no proper information. Information systems with the aim of increasing productivity and effectiveness. This research also uses qualitative research methods to understand research procedures by utilizing descriptive data in the form of written or oral statements. Information systems are a collection of methods that can make companies more competitive and get better information to make decisions. Management information systems play an important role in the dissemination of data within a business. Information for business does not only come from within the organization but also from outside. The creation of management information systems makes it easier to meet the information needs of organizational decision makers and other users. Human work can be replaced by technological advances. As a result, a secretary must continue to learn to understand technology which greatly helps organizations in their operations. Information is an important element that must be addressed immediately. Companies need accurate information to make decisions and find solutions to problems.